Model Pembelajaran Kooperatif Tipe STAD untuk Meningkatkan Hasil Belajar Pendidikan Kewarganegaraan - Indriani Hamka; Wahyudin Noe; Syaharuddin Syaharuddin; Irwan Abbas (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2025)
Cooperative learning encourages students to work together in a group to achieve learning objectives. This study aims to determine the effectiveness of the Student Teams Achievement Division (STAD) type cooperative learning model in improving learning outcomes on the material of the Gotong Royong Citizenship Project in class X IPA SMA Negeri 35 South Halmahera. The method used is Classroom Action Research (PTK) with research subjects as many as 31 students. Data obtained through documentation, tests, and observations was analyzed descriptively. The results showed a significant increase from cycle I to cycle II. Participants' learning activities increased from 46% (sufficient category) to 83% (very good category). Learning evaluation results also showed improvement: from only six learners (19%) who passed in cycle I to 29 learners (94%) in cycle II, with the average score increasing from 48 to 81. These findings support the effectiveness of the STAD model in improving participation and learning outcomes.